HUBUNGAN ANTARA PEKERJAAN IBU DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI DI MASA PANDEMI - Khoiriyah, Hikmatul Khoiriyah (Jurnal Kesehatan, 2022)
Breast milk (ASI) is an emulsion of fat in a solution of protein, lactose and organic salts secreted by the two glands of the mother's breast, which is useful as the main food for the baby. Exclusive breastfeeding based on Government Regulation Number 33 of 2012 concerning Exclusive Breastfeeding is breast milk that is given to babies from birth for six months, without adding and/or replacing with other foods or drinks (except drugs, vitamins, and minerals) (Kemenkes RI , 2020). The purpose of this study was to determine the relationship between mother's work and exclusive breastfeeding for babies during the pandemic. The research was conducted with analytical research methods, with a cross sectional approach. The population used in this study were mothers who had babies aged 6-11 months in the working area of the Ganjar Agung Health Center for the January-May 2021 period, namely 47 mothers. The results of statistical tests using the Chi Square test showed that there was a relationship between the two variables with p value = 0.000 less than = 0.05, meaning that there was a relationship between mother's work and exclusive breastfeeding. The conclusion in this study is that the mother's occupation affects exclusive breastfeeding, working mothers have limited time with their babies so they tend not to be successful in exclusive breastfeeding.Keywords : Occupation, Exclusive Beastfeeding